2017
DOI: 10.3892/etm.2017.4639
|View full text |Cite
|
Sign up to set email alerts
|

Chronic disorders of consciousness

Abstract: Abstract. Over the last 20 years, studies have provided greater insight into disorders of consciousness (DOC), also known as altered state of consciousness. Increased brain residual functions have been identified in patients with DOC due to the successful application of novel next-generation imaging technologies. Many unconscious patients have now been confirmed to retain considerable cognitive functions. It is hoped that greater insight regarding the psychological state of patients may be achieved through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
(63 reference statements)
0
10
0
2
Order By: Relevance
“…The CRS-R is a standardized behavioral assessment measure that has been widely used for diagnostic assessment and outcome measurement in patients with DOC (Gerrard et al, 2014). However, the rate of clinical misdiagnosis based on the CRS-R remains high (Xie et al, 2017). Previous results have demonstrated EEG can detect and analyze brain activity in clinical practice (Lehembre et al, 2012; Bai et al, 2017a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The CRS-R is a standardized behavioral assessment measure that has been widely used for diagnostic assessment and outcome measurement in patients with DOC (Gerrard et al, 2014). However, the rate of clinical misdiagnosis based on the CRS-R remains high (Xie et al, 2017). Previous results have demonstrated EEG can detect and analyze brain activity in clinical practice (Lehembre et al, 2012; Bai et al, 2017a,b).…”
Section: Introductionmentioning
confidence: 99%
“…A correlation analysis between tactile EEG response and patient outcome showed that patients with better outcomes, such as recovery, had a more pronounced decrease in theta rhythm PSD during tactile stimulation (trend significance: r = −0.55, p = 0.01). The increase of beta rhythm (17)(18)(19)(20) Hz) power in central areas was correlated with the thickness of paracentral (r = 0.82, p = 0.0005) and precentral (r = 0.80, p = 0.0007) areas bilaterally (Figure 6). A correlation analysis between tactile EEG response and patient outcome showed that patients with better outcomes, such as recovery, had a more pronounced decrease in theta rhythm PSD during tactile stimulation (trend significance: r = −0.55, p = 0.01).…”
Section: Correlation Of Tactile Eeg Response With Morphometric Datamentioning
confidence: 88%
“…Electroencephalography (EEG) has shown variable abnormal activity in comatose patients after TBI. Mecarelli et al showed that background activity progressively decreased in amplitude until the eventual attenuation or suppression of cortical bioelectrical activity [ 18 ]. Spindle comas accompanied pontomesencephalic junction lesions when epileptiform activity and sleep spindles appeared along with the functional preservation of the remaining EEG patterns [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A requisite for conscious behaviors is the presence of adequate arousal (i.e., wakefulness) and awareness of content (i.e., sensory, cognitive, and affective experience) ( Giacino et al, 2018 ). The first is referred to the level of consciousness and the second to the content of consciousness ( Xie et al, 2017 ; Giacino et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%